Care of People Living with Dementia in Bulgaria: Between Over-Responsibility to the Family and Distrust in Public Health Services and Policies - Goncharova Galina; Karamelska Teodora (Comparative Southeast European Studies)
Thirty years after the transition to democracy in Bulgaria, there is a lack of social and community support for people living with dementia and for their families and caregivers. Both residential and assisted living facilities in the country have remained both unpopular and underdeveloped, and based on in-depth biographical and expert interviews and focus groups, we shall discuss the subjective experience of informal caregivers of people living with dementia, accumulated in the confined space of home and family. We shall try to show how inconsistent application of the European Union’s social policies as well as the existence of enduring socio-cultural stereotypes relating to parental care places caregivers in passive, but over-responsible and implicitly critical positions towards the management both of public and private services for older people in Bulgaria.